Angie's error occurred when she stated her final result. Let's break down her steps:
-
She started with the equation:
\(-x + 7 = -11\) -
She subtracted 7 from both sides:
\(-x + 7 - 7 = -11 - 7\)
This simplifies to:
\(-x = -18\) -
The next step, which is not shown correctly in her solution, is to solve for \(x\).
To do this, multiply or divide both sides by \(-1\):
\(x = 18\)
Instead of arriving at \(x = -18\), Angie should have correctly found that:
\(x = 18\)
So, the part of the solution where Angie made an error is when calculating the final value of \(x\). The correct answer regarding where she made an error would be:
She did not divide both sides by −1.